(untitled) (Global Journal of Human-Social Science, 2010)
Nigeria is one of the Oil Producing and Exporting Countries (OPEC) whose crude oil is preferred by many non oil producing countries like Britain and the United States of America. A large percentage of Nigeria"s foreign exchange earnings is generated from the sales of crude oil. While many of the nations who buy crude oil from Nigeria are comfortable with their fuel situation, Nigeria is engulfed in incessant fuel crisis which has been taken its toll on almost all aspects of the economy for almost two decades. This is a situation when there is acute shortage of fuel with attendant long queues that last for weeks and months. When the nation is about to breathe a sigh of relief through regular supply, suddenly, the crisis will erupt again causing untold hardship for vehicle owners, commercial drivers and the general populace who depend on the availability of fuel for mobility and production of goods and services. In recent times, the crisis is further compounded by the inability of the Power Holding Company of Nigeria (PHCN) to meet the energy needs of the populace. Thus many providers of goods and services like tailors, furniture makers and others rely on fuel to generate electricity for their activities. This has resulted in the soaring prices of basic commodities and services. Against this background, this paper examines the role and concept of good governance, the trend of fuel crisis in Nigeria, causes and effects of fuel crisis and identifies ways of preventing fuel crisis in Nigeria. I.